The Role of Disaster Preparedness Agency in Flood and Landslide in Kalijompo Plantation Jember - Shodiq, M. Nur; Mulyono, Joko Nur (Laboratorium Sosiologi FISIP Universitas Jember, 2018)
Abstract Indonesia which is rich in natural landscapes such as mountains, valleys and rivers has a risk of flash floods and landslides. Risks are increasing because of the equator crossing Indonesia and the exploitation of nature by humans. These landscape characteristics, as well as the potential for flash floods and landslides, are also found in the Kalijompo Plantation, Jember Regency. thus alertness to disaster is needed. This research was conducted to describe and analyze institutions in alert to flash floods and landslides in the Kalijompo Plantation, Jember Regency. This study uses a qualitative approach through conducting interviews, documentation, and observation. Anthony Giddens' agency theory is borrowed as a theoretical approach. The findings of this study are agencies acting as facilitators, provocateurs, and motivators in disaster alertness. Agency motives in this context are social and economic. Keywords: Agency, Vigilance, Banjir Bandang, Land Slide Referensi: Buku: Giddens, Anthony. 1984. Teori Strukturasi Dasar-Dasar Pembentukan Struktur Sosial Masyarakat. Terjemahan oleh Maufur dan Daryatno. 2010. Yogyakarta:Pustaka Pelajar Giddens, Anthony. 1984. The Constitution of Society. Diterjemahkan oleh: Sujono, Adi Loka. Cetakan Keempat tahun 2011. Yokyakarrta: Topprint. Sugiyono. 2010. Metode Penelitian Kuantitatif dan Kualitatif & RND. Bandung: Alfabeta. Suyanto, Bagong dan Sutinah. 2006. Metode Penelitian Sosial: Berbagai Alternatif Pendektan. Jakarta: Kencana Prenada Media Grup. Jurnal dan Skripsi: Cahya, Deden Yoga Dwi. 2016. Peran FMU Darmaning Lestari dalam Pengurangan Risiko Bencana Tanah Longsor di Desa Darsono Kecamatan Arjasa Kabupaten Jember. Skripsi. Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jember Istifadah, Evaatul. 2017. Agensi dalam Membangun Kesadaran Lingkungan Masyarakat (Fenomenologi Aktivis Lingkungan dalam Mengolah Limbah Sampah Organik di Kampung Ujung Banyuwangi). Skripsi. Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jember Nandi. 2007. Longsor. Jurusan Pendidikan Geografi. Bandung. FPIPS-UPI. Dokumen: Direktorat Sungai dan Pantai, Direktorat Jenderal SDA Kementrian PU Bekerjasama dengan JICA. 2012. Petunjuk Tindakan dan Sistem Mitigasi Banjir Bandang. Dinas Pekerjaan Umum. Padang.